TINJAUAN FIKIH TENTANG PENTINGNYA KALENDER DALAM IBADAH - Khusurur, Misbah (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2025)
The Hijri calendar plays a crucial role in Islam as it serves as the primary reference for determining worship times, such as prayer, fasting, zakat, and hajj. This study aims to examine the sharia basis for the use of the Hijri calendar, the views of scholars of interpretation and jurisprudence (fuqaha) regarding the function of the crescent moon, and the problematic differences in methods for determining the beginning of the Hijri month in Indonesia. The study employed a qualitative approach with a library study method through content analysis of primary sources in the form of the Qur'an, classical and modern tafsir books, and hisab and rukyat literature, along with secondary sources in the form of books and academic articles. The results of the study indicate that the determination of the beginning of the Hijri month is divided into three categories, namely shahr syar'i (based on ru'yatul hilāl or istikmāl),